PENGARUH MULTINATIONALITY DAN TIMELINESS OF FINANCIAL REPORTING TERHADAP PENGHINDARAN PAJAK - Muhammad Ridwan (Universitas Pamulang, 2019)
Tax Avoidance is a step taken by many taxpayers because it doesn’t violate the law, supporting factors can be in the form of Multinationality and Timelinessn of Financial Reporting. This researchh was conductedn on companies listed on the Indonesia Stockn Exchangenduring the observation period of 2012-2016. The sampling method used was purposive samplingg method with a sample of 32 consisting of 8 manufacturing companies over a period of 4 consecutive years of observation. Based on the result of multiplee linear analys regression, the result of the study show that the Multinationality variable has non effect on the effective tax rate, while the timeliness of financial reporting has a negative effect on the effective tax rate